(untitled) (Bangladesh Critical Care Journal, 2015)
Background: Acute kidney injury (AKI) is a common and serious complication among patients admitted in intensive care units (ICUs). The incidence, cause, severity and outcome of AKI in Bangladeshi ICUs is largely unknown. The aim of this study was to find out the cause of AKI among the hemodynamically unstable patients requiring SLED admitted to the ICU of BIRDEM Hospital, Dhaka, Bangladesh. Methods: All critically ill patients of AKI admitted to the 10 bed mixed adult ICU over a period of a year were studied prospectively if they needed SLED. Standard demographic, physiologic and clinical data were collected. Severity of illness was assessed using acute physiology and chronic health evaluation (APACHE) II score. Diagnosis of AKI was based on Acute Kidney Injury Network (AKIN) criteria. Results: 43 hemodynamically unstable patients with AKI were studied. Mean age of the patients were 60.12 ± 14.57 with 67.4% male patients. 35% patients had de novo AKI where as 65% had acute on chronic renal failure. There was high prevalence of DM (72.1%) and HTN (60.5%) among study patients. Septic shock (48.83%) and cardiac cause including acute myocardial infarction and/or cardiogenic shock (46.51%) were the two commonest causes of AKI in our ICU. Conclusion: Higher age, pre-existing chronic renal impairment, DM and HTN were associated with AKI with hemodynamic instability requiring SLED. Sepsis is the commonest cause of AKI followed by cardiac causes. As expected, sicker patients with high APACHE II score were more likely to develop AKI. However, a larger scale study should be done including all hemodynamically unstable AKI patients admitted in different ICUs of Bangladesh Bangladesh Crit Care J September 2014; 2 (2): 68-70